Photothermal hydrocarbon synthesis using alumina-supported cobalt metal nanoparticle catalysts derived from layered-double-hydroxide nanosheets. (June 2019) - Li, Zhenhua; Liu, Jinjia; Zhao, Yufei; Shi, Run; Waterhouse, Geoffrey I.N.; Wang, Yuanshen; Wu, Li-Zhu; Tung, Chen-Ho; Zhang, Tierui
Abstract: The photothermal conversion of syngas (CO and H2 ) offers a relatively straightforward method for the production of solar fuels with high solar-to-fuel conversion efficiencies. Herein, we report the successful synthesis of a series of novel Co-based catalysts via hydrogen reduction of CoAl layered-double-hydroxide (LDH) nanosheets at temperatures( x ) in the range 300–700 °C. With increasing reduction temperature, the selectivity of the Co- x catalysts for photothermal CO hydrogenation under UV-vis irradiation shifted progressively from CH4 to high-value hydrocarbons, with the Co-700 catalyst affording a remarkable C2 + selectivity of 65% (∼36.3% C2-4 vs ∼28.7% C5 + ) at a CO conversion of 35.4%. High-resolution transmission electron microscopy, X-ray diffraction and Co K-edge extended X-ray absorption fine structure analyses revealed the Co-700 catalyst contained metallic Co nanoparticles supported by amorphous alumina, whilst density functional theory calculations revealed that metallic Co nanoparticle formation improved the C-C coupling ability of the LDH-derived catalysts, thus enhancing the selectivity to higher hydrocarbons. This study further highlights the great promise of photothermal catalytic systems for CO conversion to fuels and other valuable chemicals feedstocks. Graphical abstract: Image 1 Highlights: A facile strategy to controllable synthesis of a series of Co-based catalysts by H2 reduction of CoAl-LDH - was developed. The FTS of the Co- x catalysts were evaluated under solar irradiation, with a shift in product selectivity from CH4 to C2 + . DFT calculations revealed that the formation of Co nanoparticles is a key factor for efficient C-C coupling. Results pave the way for the development of other photothermal catalysts for solar-driven FTS reactions.